Water demand management at rural area using Micro-Component Analysis: A case study at Kenyir Lake, Malaysia - Azlan N.N.I.M.; Saad N.M.; Norhisham S.; Malek M.A.; Shkuri N.S.M.; Zolkepli M.; Ean L.W.; Mohamad A.M. (IOP Publishing Ltd, 2023)
Water is one of the cornerstones in human survival and a necessity for socio-economic development. Due to that, effective management of water demand especially in the rural area becomes vital. The objective of this study is to conduct a water demand study at Kenyir Lake, Terengganu using Micro-Component Analysis (MCA). Water demand is also being assessed using National Water Services Commissions (SPAN) Guidelines, parallel to water guidelines applied for Malaysia's building and comparison purposes. MCA considers detailed parameters of water use activities of the respective study area, whereas SPAN Guidelines use the fixed values of average daily water demand according to the type of building. The available dataset was interpreted using MCA and SPAN Guidelines, resulting in total daily water demand at Kenyir Lake of 1249.8 m3 and 1254.1 m3 respectively. Estimated water demand using SPAN Guidelines is found to be higher than MCA. The value differences occur due to the average water demand value in the guideline that is limited to a specific type of premises and does not comply with premises there. The estimated water demand can be adopted as a baseline for water companies and the government to improve the demand and supply of water. Published under licence by IOP Publishing Ltd.